2008
DOI: 10.1093/nar/gkn891
|View full text |Cite
|
Sign up to set email alerts
|

Novel bimodular DNA aptamers with guanosine quadruplexes inhibit phylogenetically diverse HIV-1 reverse transcriptases

Abstract: DNA aptamers RT5, RT6 and RT47 form a group of related sequences that inhibit HIV-1 reverse transcriptase (RT). The essential inhibitory structure is identified here as bimodular, with a 5′ stem–loop module physically connected to a 3′-guanosine quadruplex module. The stem–loop tolerates considerable sequence plasticity. Connections between the guanosine triplets in the quadruplex could be simplified to a single nucleotide or a nonnucleic acid linker, such as hexaethylene glycol. All 12 quadruplex guanosines a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 58 publications
(101 reference statements)
6
82
0
Order By: Relevance
“…It has been also shown that engineered aptamers like multivalent circular constructs exhibit increased stability against cleavage by exonucleases and improved (2 to 3-fold) anticoagulant activity in comparison with canonical single stranded aptamers [8]. Increased inhibitory activity against HIV-1 reverse transcriptase has been shown also for recently reported bimodular DNA aptamers [7].…”
Section: Accepted M Manuscriptmentioning
confidence: 89%
See 1 more Smart Citation
“…It has been also shown that engineered aptamers like multivalent circular constructs exhibit increased stability against cleavage by exonucleases and improved (2 to 3-fold) anticoagulant activity in comparison with canonical single stranded aptamers [8]. Increased inhibitory activity against HIV-1 reverse transcriptase has been shown also for recently reported bimodular DNA aptamers [7].…”
Section: Accepted M Manuscriptmentioning
confidence: 89%
“…Nowadays, increased interest in aptamer research is focused on improvement of these features for application in medical therapy, biotechnology and biosensor development [3,4]. A novel approach in aptamer engineering is based on dimerization [5][6][7] or multimerization [8], which possess two or more binding sites for the target ligand. Among DNA aptamers, those sensitive to thrombin are most studied.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, some sequences do not act through base pairing but as aptamers. These aptamers fold into defined three-dimensional (3D) structures and interact with HIV-1-associated proteins, such as HIV-1 reverse transcriptases (6,7), RNase H (8), Tat proteins (9), integrase (10)(11)(12)(13), and surface glycoproteins (14,15). A subcategory of aptamers possess an additional intermolecular assembly feature such as the quadruplex d(TGGGAG) 4 described by Hotoda et al, which was assembled by four 6-mer G-rich sequences in parallel with the 5=-end attaching to aromatic substituents of adequate size, such as tert-butyldiphenylsilyl (TBDPS) and 4=4-dimethoxytriphenyl (DMT) (16)(17)(18)(19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…Protein targeted DNA aptamers Thrombin (TBA), sensitive to fibrinogen binding site GGTTGGTGTGGTTGG Bock et al 1992;Padmanabhan et al 1993 Thrombin, sensitive to heparin binding site GGTAGGGCAGGTTGG* Tasset et al 1997 HIV integrase 93del GGGGTGGGAGGAGGGT Jing and Hogan 1998;Jing et al 2000;De Soultrait et al 2002;Phan et al 2005;Chou et al 2005 HIV-1 reverse transcriptase GGGGGTGGGAGGGTAGGCCTTAGG TTTCTGA Andreola et al 2001 HIV-1 reverse transcriptase CGCCTGATTAGCGATACTCAGCGTT GGGGGGGGGGGG Michalowski et al 2008 HIV-1 nucleocapsid protein GGTTGGTGTGGTTGG Kankia et al 2005 Anti HIV activity Unknown specific target T30177 GTGGTGGGTGGGTGGGT Mukundan et. al.…”
Section: Target/name Sequence Of Aptamer ( 5´ → 3´) Referencesmentioning
confidence: 99%
“…Aptamers include those which exhibit sensitivity to envelope Gp120 protein (Wyat et al 1994), HIV integrase (Chou et al 2005 and references herein) and HIV reverse transcriptase (Michalowski et al 2008 and references herein). The dissociation constant of these aptamers was in the nM range (see Table 1 for nucleotide sequence of aptamers).…”
Section: For Detailed Review)mentioning
confidence: 99%